2021
DOI: 10.3934/naco.2020057
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid AGWO-PSO algorithm in mitigation of power network oscillations with STATCOM

Abstract: The assimilation of flexible AC transmission (FACTS) controllers to the existing power network outweigh the numerous alternatives in enhancing the damping behavior for the inter-area /intra-area system oscillations of a power network. This paper provides a rigorous analysis in damping of oscillations in a power network. It utilizes a shunt connected voltage source converter (VSC) based FACTS device to enhance the system operating characteristics. A comprehensive system mathematical modelling has been developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…To tackle this issue, for the efficient search capability and balance between exploration and exploitation [27][28][29], weights have been defined in the proposed WGWO approach. Hence, the position update function can be derived using (4).…”
Section: Proposed Wgwo Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…To tackle this issue, for the efficient search capability and balance between exploration and exploitation [27][28][29], weights have been defined in the proposed WGWO approach. Hence, the position update function can be derived using (4).…”
Section: Proposed Wgwo Algorithmmentioning
confidence: 99%
“…The role of automatic voltage regulators (AVRs), power system stabilizers (PSSs) is vital, where placements of flexible alternating current transmission system (FACTS) controllers have also been recommended in the literature. The parameter settings of these controllers play also a prominently vital role, for which various tuning algorithms are proposed in the literature [4,5]. It has been observed that there are various novel methods proposed in the literature for effective damping of low-frequency power oscillations in a power network.…”
Section: Introductionmentioning
confidence: 99%
“…The wolves' hunting strategy and position updating strategy are balanced by some crucial mathematical parameters that provide a rich diversification and intensification methodology in mapping the search space for the best possible solution. Moreover, GWO eliminates the possible demerits of getting stuck in local minima and a larger number of tuning parameters 31–34 . Hence, GWO is preferred over other meta‐heuristic algorithms.…”
Section: Application Of Meta‐heuristic Algorithms For Mppt Under Partial Shadingmentioning
confidence: 99%